Systematic Literature Review of Boss Phubbing From 2013 – 2023 - Irfan Hadi Yuda; Joko Suyono (CV. Syntax Corporation Indonesia, 2024)
This study conducted a systematic literature review analysis to examine the growing research around the phenomenon of boss phubbing from 2013 to 2023. Boss phubbing refers to bosses doing phone snubbing, which has the potential to impact workplace dynamics and employee well-being. Through a systematic review of academic literature, this study aims to identify the main themes, article information, and content of article extraction. To provide a comprehensive review of boss phubbing, nine English-language research articles were generated between 2013 and 2023 from the Scopus database. Data were analyzed using Watase, presented by descriptive analysis and content analysis. This research contains a discussion of the theory that underlies the article so as to provide insight to understand the direction of research and its potential implications for organizational behavior and management practices. This research is also complemented by ideas for future developments in the topic, thus encouraging the need for future research to investigate more deeply whether certain manifestations of Boss Phubbing can provide positive results for individuals, teams, or organizations.